Optimalisasi Pengelolaan Perpustakaan Sekolah melalui Pelatihan Manajemen Berbasis Digital di SD Muhammadiyah 16 Palembang - Samsilayurni Samsilayurni; Sri Utami; Gunawan Ismail; Yuniar Pratiwi; Eka Apriani (Lamahu: Jurnal Pengabdian Masyarakat Terintegrasi, 2026)
The digital transformation of education requires school libraries to evolve into technology-based learning resource centers. However, library management at SD Muhammadiyah 16 Palembang was still dominated by conventional administrative practices, limiting the effectiveness of library services in supporting teaching and learning activities. This community service program aimed to optimize school library management through digital-based management training for library personnel. The program was implemented through five stages: needs assessment, training, hands-on practice, mentoring, and evaluation. The training covered digital library management, the use of the Online Public Access Catalog (OPAC), digital collection management, literacy promotion, and the integration of digital learning resources into library services. Program evaluation was conducted using observations, interviews, documentation, and pre- and post-training assessments. The results showed that participants' competencies improved significantly, with 80% of participants able to operate digital library applications and apply digital management practices in library services. The program also encouraged the development of more effective, accessible, and interactive library services, strengthening the role of the school library as a technology-supported learning resource center.